INTRARETINAL HYPERREFLECTIVE FOCI IN BEST VITELLIFORM MACULAR DYSTROPHY. Issue 12 (December 2018) - Parodi, Maurizio Battaglia; Romano, Francesco; Sacconi, Riccardo; Casati, Stefano; Marchini, Giorgio; Bandello, Francesco; Iacono, Pierluigi
Abstract : Purpose: To report on the presence of hyperreflective foci (HF) on spectral domain optical coherence tomography in patients with Best vitelliform macular dystrophy (BVMD), and to describe the relationship between HF and stages of the disease. Methods: Consecutive patients diagnosed with BVMD were enrolled in a prospective cross-sectional study. All patients and control subjects underwent a complete ophthalmologic examination, including best-corrected visual acuity and spectral domain optical coherence tomography. Main outcome measure: identification of HF in BVMD. Secondary outcome: assessment of the HF in each stage and correlation with best-corrected visual acuity. Results: Overall, 75 eyes of 39 patients were included in the study (Stage 1: 13%, Stage 2: 43%, Stage 3: 15%, Stage 4: 21%, and Stage 5: 8%). On spectral domain optical coherence tomography assessment, intraretinal HF were present in 83% of all eyes, in 91% of eyes affected by clinical BVMD (Stages 2–5) and in 100% of patients in Stages 4 and 5. In 46% of clinically diseased eyes, HF were localized in the fovea and in correspondence with the BVMD lesions at the level of the outer nuclear layer and outer plexiform layer. Hyperreflective foci were present in 16% of control eyes. Mean number of HF in eyes affected by clinical BVMD stood at 7.67 ± 7.35. These were predominantly small HF (6.23 ± 6.14, P < 0.001) localized in the outer nuclear layer (5.19 ± 5.38, P = 0.001) and presented largely in the extrafoveal, rather than the foveal area (5.21 ± 5.57 vs 2.46 ± 2.73, P = 0.001). Analysis of HF distribution revealed that the control group and Stage 1 eyes had the fewest HF; Stage 4 displayed a significant increase in the number of HF compared with Stages 2 and 3; Stage 5 also showed an increased number of HF, although this difference was statistically significant only with Stage 3 eyes. The best-corrected visual acuity was negatively related to the number of HF, with best-corrected visual acuity deteriorating as the number of HF increased in Stages 2 to 5 ( P < 0.001). Conclusion: This study describes the presence of HF in BVMD using spectral domain optical coherence tomography. Our data suggest that HF identification is correlated with the progression of the disease and could represent a useful biomarker of BVMD. Abstract : Hyperreflective foci are a new morphologic entity described in association with many retinal disorders. The authors' study provides evidence of a correlation linking hyperreflective foci with the progression of the disease and visual acuity deterioration in Best vitelliform macular dystrophy.